Learn design patterns with Java (Packt, 2018)
"Design Patterns give a software developer an array of tried and tested solutions to common problems, thus reducing the technical risk to the project by not having to employ a new and untested design. This course is a practical guide to learning design pattern with 100% coding involved. We encourage users to do coding in parallel while learning the course. In this course, you will start by exploring the benefits of using design patterns for developers in their regular development environment. You will move on to see which design patterns are suited for which circumstances. You will see the different categories to which the Design Patterns belong. Throughout this course, each type of Design Pattern will be accompanied by a practical example and information on when to use a given Design Pattern. You will also be shown scenarios in which specific Design Patterns are to be avoided. In the end, you will learn how to overcome any issues that may be encountered while using design patterns initially."--Resource description page